2019
DOI: 10.47114/j.agroped.2017.jun8
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variability of Major and Micro Nutrients in Soils of Bhandara District of Maharashtra

Abstract: The georeferenced surface soil samples from Bhandara district of Maharashtra were collected using Global Positioning System (GPS) to study the variability in availability of N, P, K, S, Zn, Fe, Cu, Mn and B. The fertility maps were prepared using Geographical Information System for each nutrient. The results revealed that soil reaction is acidic to slightly alkaline (4.16 to 8.35), whereas organic carbon content varied from very low to very high (0.65 to 1.43 g kg-1). The available nitrogen ranged from 73.8 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Similar observations were also reported in rice growing soils of Birbhum district in West Bengal [15]. Katkar et al [16], Patangray et al [17] and Zalte et al [18] also reported similar ranges of available N in the soils of Bhandara, Yavatmal and Amravati (Chikhaldara tehsil) districts of Maharashtra.…”
Section: Available Macronutrient Status Of Soilsupporting
confidence: 75%
“…Similar observations were also reported in rice growing soils of Birbhum district in West Bengal [15]. Katkar et al [16], Patangray et al [17] and Zalte et al [18] also reported similar ranges of available N in the soils of Bhandara, Yavatmal and Amravati (Chikhaldara tehsil) districts of Maharashtra.…”
Section: Available Macronutrient Status Of Soilsupporting
confidence: 75%
“…Micronutrients are important for maintaining soil health and increasing use efficiency of major nutrients and ultimately the crop productivity. The deficiency of micronutrients has become major constraint in sustainable crop productivity of soils and hence there is need to know the status of nutrients of the soil (Katkar et al, 2018). Keeping this in view, the present study aims to analyze the fertility level of the soil with the help of N. P. and K. and micronutrient to recommend essential nutrients wherever necessary in the Jalgaon district.…”
Section: Introductionmentioning
confidence: 99%
“…Micronutrients are important for maintaining soil health and increasing use efficiency of major nutrients and ultimately the crop productivity. The deficiency of micronutrients has become major constraint in sustainable crop productivity of soils and hence there is need to know the status of nutrients of the soil (Katkar et al, 2018). Keeping this in view, present study was undertaken in Jalgaon district of Maharashtra to study micro and secondary nutrient status of the soils and to identify areas of nutrient deficiencies.…”
Section: Introductionmentioning
confidence: 99%